A picture book of Sojourner Truth - Adler, David A.; Griffith, Gershom (New York : Holiday House, 2001)
An introduction to the life of the woman born into slavery who became a well-known abolitionist and crusader for the rights of African Americans in the United States.
G8
Keywords: Truth, Sojourner, -- d. 1883 -- Juvenile literature; Truth, Sojourner, -- d. 1883.; African American abolitionists -- Biography -- Juvenile literature; Abolitionists -- United States -- Biography -- Juvenile literature; Social reformers -- United States -- Biography -- Juvenile literature; Abolitionists; Reformers; African Americans -- Biography; Women -- Biography